2017
DOI: 10.1038/s41598-017-10291-4
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation phenomena in Al-Zn-Mg alloy matrix composites reinforced with B4C particles

Abstract: To provide insight into precipitation phenomena in age-hardening Al-Zn-Mg(-Cu) matrix composites, an Al 7075 alloy composite reinforced with B4C particles was selected as a model system. The bulk composites were fabricated via plasma activated sintering and followed by a peak aged (T6) heat treatment. Two types of Al matrix zones were identified in the composite: (1) the regions in the vicinity of the matrix/reinforcement interface, defined as “matrix plastic zone” (MPZ) hereafter, and (2) the regions away fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…There is a large interest in age-hardenable Al-Zn-Mg alloys (7xxx series) due to their technological and practical importance, as these alloys can be treated to have a preferable combination of ductility and strength, as well as reasonable weldability and corrosion resistance. If a supersaturated Al-Zn-Mg alloy is aged under different conditions, various metastable and stable precipitates may form [1][2][3][4][5][6][7][8]. Therefore, aging can be used for tailoring the mechanical behavior of these alloys.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large interest in age-hardenable Al-Zn-Mg alloys (7xxx series) due to their technological and practical importance, as these alloys can be treated to have a preferable combination of ductility and strength, as well as reasonable weldability and corrosion resistance. If a supersaturated Al-Zn-Mg alloy is aged under different conditions, various metastable and stable precipitates may form [1][2][3][4][5][6][7][8]. Therefore, aging can be used for tailoring the mechanical behavior of these alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoindenation hardness values in the vicinity of the B 4 C/Al interface (4.32 ± 0.64 GPa) are higher than those in the Al matrix regions that are far away from the interface ( x > 1 μm, 3.95 ± 0.36 GPa). The increase in local hardness as the location approaches the B 4 C/Al interface is attributed to the plastic deformation zone (stress field) and the accelerated precipitation behavior in the vicinity of the interface …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been found that the precipitation behavior changes with a reduction in grain size, and thus conventional heat treatments are not as effective as they are in the conventional coarse grained alloys . In recent studies on bulk B 4 C/Al 7000 series composites after T6 temper, relatively coarser η' precipitates and rod‐like η phase were observed in the vicinity of the B 4 C/Al interface compared to the GP zones and fine η' precipitates in the Al matrix regions that are far away from the interface . These observations indicated accelerated precipitation kinetics occurred at the interfacial regions due to the presence of the B 4 C particles.…”
Section: Introductionmentioning
confidence: 99%
“…An accelerated aging response was reported in a number of composite systems, e.g., B 4 C/Al-Zn-Mg alloy [15], SiC p /2014Al [16], and SiC w /Al-Li alloys [17,18]. A mechanism proposed to explain the accelerated aging in AMCs was related to the enhanced nucleation and/or growth of precipitates in the heavily dislocated matrix regions adjacent to the reinforcement [19,20].…”
Section: Introductionmentioning
confidence: 93%
“…Generally, the precipitation behavior of AMCs depends on the matrix material, type of reinforcements, processing route and aging temperature [11][12][13][14]. Previous studies indicated that the precipitation sequence in AMCs remained the same as the matrix alloys, but the aging kinetics was observed to be changed [5,15].…”
Section: Introductionmentioning
confidence: 99%